2011
DOI: 10.1021/ol201734w
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct Cross-Coupling Reaction of Glycals with Activated Alkenes

Abstract: An efficient method for a Pd(OAc)(2)-catalyzed cross-coupling reaction of glycals with activated alkenes under mild conditions has been developed. This transformation provides an expedient synthetic method to C(2)-functionalized glycals, which are common structural building blocks in natural products and other biologically active compounds. The reaction scope includes different kinds of carbohydrates, protecting groups and substituents on alkene. Moderate to excellent yields and pure E configuration selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The first example of this type of reactivity was reported by Liu et al. in 2011 and involved the coupling of glycals with substituted alkenes [60] . The best conditions require the use of catalytic quantities of Pd(OAc) 2 and the presence of Cu(OTf) 2 , in a mixture of solvents (dimethylacetamide (DMA)/AcOH=1:1) under an atmosphere of O 2 (Scheme 25, conditions A).…”
Section: New Emerging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first example of this type of reactivity was reported by Liu et al. in 2011 and involved the coupling of glycals with substituted alkenes [60] . The best conditions require the use of catalytic quantities of Pd(OAc) 2 and the presence of Cu(OTf) 2 , in a mixture of solvents (dimethylacetamide (DMA)/AcOH=1:1) under an atmosphere of O 2 (Scheme 25, conditions A).…”
Section: New Emerging Methodsmentioning
confidence: 99%
“… Pd II ‐catalyzed C2‐vinyl glycosides reported by Liu et al [60] . BQ: p ‐benzoquinone, pc: phthalocyanine.…”
Section: New Emerging Methodsmentioning
confidence: 99%
“…Recently, Liu and co‐workers reported a palladium‐catalyzed method for the alkenylation of glycals with activated alkenes 5i. This method works very well with glycals, which are fairly stable molecules and activated olefins as coupling partners.…”
Section: Methodsmentioning
confidence: 99%
“…By far the most commonly used substrates for C–H functionalization at C2 are glycals, and most of this chemistry has been developed within the last decade. Liu and co‐workers used palladium‐catalyzed cross‐coupling to couple glycals (e.g., 56 ) with activated alkenes and thereby to achieve easy access to C‐functionalization of C2 without losing the alkene functionality (Scheme ) . The conditions were optimized and it was found that Pd(OAc) 2 (10–20 %) together with Cu(OTf) 2 as the oxidant gave the highest yield at 70 °C with use of DMA/AcOH as the solvent mixture.…”
Section: C–h Functionalization Of C2–h To C6–hmentioning
confidence: 99%